Identification of far-red light acclimation in an endolithic Chroococcidiopsis strain and associated genomic features: Implications for oxygenic photosynthesis on exoplanets - Billi, Daniela; Napoli, Alessandro; Mosca, Claudia; Fagliarone, Claudia; de Carolis, Roberto; Balbi, Amedeo; Scanu, Matteo; Selinger, Vera M.; Antonaru, Laura A.; Nürnberg, Dennis J. (Frontiers in Microbiology, 2022)
Deserts represent extreme habitats where photosynthetic life is restricted to the lithic niche. The ability of rock-inhabiting cyanobacteria to modify their photosynthetic apparatus and harvest far-red light (near-infrared) was investigated in ten strains of the genus Chroococcidiopsis, isolated from diverse endolithic and hypolithic deserts communities. The analysis of their growth capacity, photosynthetic pigments and apcE2-gene presence revealed that only Chroococcidiopsis sp. CCMEE 010 was capable of far-red light photoacclimation (FaRLiP). 15 FaRLiP genes were identified, encoding paralogous subunits of photosystem I, photosystem II and the phycobilisome, along with three regulatory elements. CCMEE 010 is unique among known FaRLiP strains by undergoing this acclimation process with a significantly reduced cluster, which lacks major photosystem I paralogues psaA and psaB. The identification of an endolithic, extremotolerant cyanobacterium capable of FaRLiP contributes to our appreciation of this phenotype’s distribution in nature, but it also has implications for the possibility of oxygenic photosynthesis on exoplanets.